Organisational leadership in transforming economies: Leadership, management and national culture in selected countries of Central and Eastern Europe - Vincent Edwards (Journal for East European Management Studies, 2003)
The paper presents the results of a survey of managers in seven countries of CEE, focusing on leadership and management, the degree of deference subordinates display towards senior managers, work and leisure, and ethical issues. In discussing the findings of the survey particular attention will be paid to similarities and differences revealed by the responses of the managers in the various countries. – – Der Artikel zeigt die Ergebnisse einer Umfrage unter Managers in sieben Ländern Ostmitteleuropas im Bereich von Führung und Management, dem Ausmaß an Achtung Untergebener gegenüber Vorgesetzten, Arbeit und Freizeit und ethischen Belangen auf. Bei der Diskussion der Befunde wird besondere Aufmerksamkeit auf Gemein-samkeiten und Unterschiede in den Antworten der Manager aus den verschiedenen Ländern gelegt.
Keywords: 650; Organisational leadership; Central and Eastern Europe; management; national culture